Позывные из ночи: [докум.] повесть о разведчиках / Ис. Бацер, А. И. Кликачев ; [худож. Н. И. Брюханов] - Бацер Исаак Маркович (Карелия, 1977)
Экземпляры: КХ (20120808) / Инвентарный номер: 661777 / Цена: 1.15 / Сис.шифр: 9(С)27 / Авт.знак: Б 31 / ГРНТИ: 03 / ББК: 63